2017
DOI: 10.3390/s17050952
|View full text |Cite
|
Sign up to set email alerts
|

Mining Productive-Associated Periodic-Frequent Patterns in Body Sensor Data for Smart Home Care

Abstract: The understanding of various health-oriented vital sign data generated from body sensor networks (BSNs) and discovery of the associations between the generated parameters is an important task that may assist and promote important decision making in healthcare. For example, in a smart home scenario where occupants’ health status is continuously monitored remotely, it is essential to provide the required assistance when an unusual or critical situation is detected in their vital sign data. In this paper, we pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It encompasses a wide range of services, including personal care, healthcare, social engagement, and smart home assistance, to meet diverse needs while strengthening social connections [ 12 ]. Secondly, regarding the analysis of user needs, Ismail et al administered a telemedicine satisfaction survey and discovered that elderly individuals who aged at home had higher telemedicine satisfaction than those living in nursing homes [ 34 ]. In addition, Bai et al found different levels of need in catering, cleaning assistance, and remote care using a study of intelligent home care users in Wuhan [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It encompasses a wide range of services, including personal care, healthcare, social engagement, and smart home assistance, to meet diverse needs while strengthening social connections [ 12 ]. Secondly, regarding the analysis of user needs, Ismail et al administered a telemedicine satisfaction survey and discovered that elderly individuals who aged at home had higher telemedicine satisfaction than those living in nursing homes [ 34 ]. In addition, Bai et al found different levels of need in catering, cleaning assistance, and remote care using a study of intelligent home care users in Wuhan [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efficient methods of data mining are necessary for better decision-making in this context. Many researchers have focused on investigating data mining solutions for IoT and sensor systems, including works such as: "Detecting Incremental Frequent Subgraph Patterns in IoT Environments" [3], "Mining Productive-Associated Periodic-Frequent Patterns in Body Sensor Data for Smart Home Care" [4], and "Mining Algorithm for Discovering Sequential Pattern in Wireless Sensor Network Environments" [5].…”
Section: Introductionmentioning
confidence: 99%